Investigating parental involvement and barriers shaping students’ English learning outcomes in the United Arab Emirates - Areej ElSayary; Ghadah Al Murshidi; Noor Aisha; Maxwell Peprah Opoku; Ahmed Al Zaabi (Studies in English Language and Education, 2026)
This study investigates how parental involvement (PI) influences students’ English language learning outcomes in the United Arab Emirates (UAE). Using a quantitative design, data were collected from 328 parents (69% mothers and 31% fathers) selected through randomized sampling across all seven emirates, representing diverse educational, social, and employment backgrounds. The study employed hierarchical multiple regression, linear regression, and mediation analysis to examine the predictive and indirect effects of parental engagement and barriers on English language achievement. The findings reveal that parental school involvement, homework follow-up, and parent-teacher interaction significantly enhance students’ English proficiency, with homework monitoring having the strongest effect, followed by parent-teacher interaction and school involvement. In contrast, parental barriers, such as time constraints, limited communication opportunities, and institutional obstacles, negatively affected students’ learning outcomes. Mediation analysis further confirmed that school-related challenges partially mediated the relationship between PI and English achievement, emphasizing the indirect effects of structural obstacles on learning performance. These findings underline that enhancing home–school partnerships and reducing institutional barriers can meaningfully strengthen students’ English language development. The study concludes with practical recommendations for policymakers, school leaders, and educators to design inclusive strategies that promote sustained parental engagement and equitable access to quality English education across the UAE. The study recommends structured parental engagement programs and school-based communication strategies to strengthen home–school partnerships and sustain English language achievement.